PENGEMBANGAN INSTRUMEN ASESMEN KETERAMPILAN INQUIRY LABORATORY SISWA SMA PADA PERMASALAHAN BIOLOGI - Rahmawati, - (2023)
This study aims to develop an inquiry laboratory skills assessment. The assessment tool developed is in the form of multiple choice questions and performance in the form of tasks and rubrics. This study used a mixed method of exploratory method. The research subjects were 264 students from 7 schools. The sample schools used were state high schools in Banten Province with purposive sampling technique. Based on the results of empirical validity using the Rasch model through the Quest program version 2.1, the percentage of questions received was (≥90%) and revised by (≥10%). The percentage of the difficulty level of the questions is 93% and the easy is 7%. Meanwhile, the percentage of different items is good at 60%, enough is 26%, and less is 13%. The level of reliability is categorized as high reliability (0.62). The level of validity of the performance assessment based on V Aiken's is declared valid. The reliability value of the performance assessment tool is 0.778. Based on this, it is known that the ICC (Interclass Correlation Coefficient) value is categorized as moderate or moderate reliability. Based on the proportion correct data, it is known that the laboratory inquiry ability is the highest on indicators measuring metrically (39.8%) and the lowest on indicators using technology and mathematics during investigations (27.8%). This research produces a product in the form of an assessment that is used as an assessment of learning, assessment for learning and diagnostic assessment for learning purposes. However, the assessment tools need to be adjusted and modified according to the conditions and situations in the school.